Effect of tsetse control with insecticide-impregnated traps on trypanosome prevalence and productivity of cattle and sheep in northern Cote d'Ivoire - Coulibaly, L.; Rowlands, G.J.; Authié, Edith; Hecker, P.A.; D'Ieteren, G.D.M.; Krebs, H.; Leak, S.G.A.; Rarieya, J.M. (OAU/STRC, 1995)
Nineteen herds of cattle (N'Dama, Baoule and Zebu crosses) and 20 flocks of Djallonke and Djallonke x Sahel sheep in the region of Boundiali, northern Cote d'Ivoire, were monitored monthly for body weight, packed red blood cell volume and the presence of trypanosomes in blood over various periods from January 1984 to December 1992. A tsetse-control campaign using alpha-cypermethrin insecticide-impregnated traps was introduced in January 1988. Tsetse control reduced tsetse relative density by over 95 percent. This resulted in a corresponding reduction in prevalence of T. congolense of over 90 percent in both sheep and cattle over the period 1988 to 1992. Average reductions in prevalence of T. vivax were lower, on average 65 percent in adults and 83 percent in young animals. T. vivax was the predominant species affecting calves, and the reduction in prevalence of this species due to tsetse control was significantly associated with increases in growth rate.